Evaluation of the impact of utilizing people's business credit on rice cultivation farmers' group - Dasipah, Euis; Nataliningsih, Nataliningsih; Gantini, Tuti; Suseno, Gijanto Purbo; Triana, Rina (Edelweiss Applied Science and Technology, 2025)
Indonesia is an agrarian country with the majority of its population engaged in farming activities. One of the primary challenges faced by farmers is the limited capital available to initiate and expand their businesses. To address this issue, the government launched the People's Business Credit (KUR) program, which serves as a financing facility for small enterprises, including farmers. This study aims to analyze the factors influencing rice farmers' participation in Cianjur Regency in utilizing KUR facilities and the impact of this participation on their farming businesses. The research employs a descriptive verification method with a quantitative approach. The findings indicate that farmer participation in KUR is significantly affected by factors such as the prohibition of usury, ease of access, and the availability of initial capital. Conversely, variables like farming experience, land area, and grain selling prices do not have a significant influence on participation. The utilization of KUR has been shown to enhance the quality of production and increase the income of rice farmers. These results provide valuable insights for the government to improve KUR distribution policies, making them more effective in boosting the economy of small rural communities.